Глаголы инхоативного способа действия в русском и литовском языках - Галнайтите, Э. (Kalbotyra, 1987)
The majority of inchoative verbs in Russian and Lithuanian derive from adjectives and (on a lesser scale) from nouns by means of suffixes (e. g. крепнуть - stiprėti, каменеть - akmenėti); a number of inchoatives are simplex verbs (e. g. таять - tirpti). All inchoatives express a gradual transition from one state into another, and aspectually they are imperfective verbs.